1991
DOI: 10.1161/01.cir.83.6.2038
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled nitric oxide. A selective pulmonary vasodilator reversing hypoxic pulmonary vasoconstriction.

Abstract: Background. The gas nitric oxide (NO) is an important endothelium-derived relaxing factor, inactivated by rapid combination with heme in hemoglobin. Methods and Results. Awake spontaneously breathing lambs inhaled 5-80 ppm NO with an acutely constricted pulmonary circulation due to either infusion of the stable thromboxane endoperoxide analogue U46619 or breathing a hypoxic gas mixture. Within 3 minutes after adding 40 ppm NO or more to inspired gas, pulmonary hypertension was reversed. Systemic vasodilation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
428
3
13

Year Published

1994
1994
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,040 publications
(455 citation statements)
references
References 35 publications
11
428
3
13
Order By: Relevance
“…Although the mechanism of this effect is unclear, it is conceivable that inhalation with NO-gasiinhibits the formation of NO, and hence NO2-, by alveolar macrophages and polymorphonuclear leucocytes. The finding that NO inhalation alone did not prevent the rise in plasma NO2-between 120 and 180 min may well be due to the fact that inhalation with NO-gas for several hours may itself result in an accumulation of NO2-in the plasma (Forstell et al, 1991). NO-gas inhalation therapy, but not infusion of L-NMMA prevented the high mortality caused by endotoxaemia in the pig.…”
Section: Mortalitymentioning
confidence: 91%
“…Although the mechanism of this effect is unclear, it is conceivable that inhalation with NO-gasiinhibits the formation of NO, and hence NO2-, by alveolar macrophages and polymorphonuclear leucocytes. The finding that NO inhalation alone did not prevent the rise in plasma NO2-between 120 and 180 min may well be due to the fact that inhalation with NO-gas for several hours may itself result in an accumulation of NO2-in the plasma (Forstell et al, 1991). NO-gas inhalation therapy, but not infusion of L-NMMA prevented the high mortality caused by endotoxaemia in the pig.…”
Section: Mortalitymentioning
confidence: 91%
“…Inhaled nitric oxide (iNO; INOmax ® , INO Therapeutics, Hampton, NJ, USA) selectively dilates the pulmonary vasculature, rapidly diffuses across the alveolar-capillary membrane, and binds to hemoglobin with minimal systemic effects [1,2]. In pivotal studies of late preterm and term neonates with hypoxic respiratory failure (HRF) and pulmonary hypertension (PH), iNO therapy has been shown to improve oxygenation and reduce the need for extracorporeal membrane oxygenation [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…1,2,5,6 Inhaled nitric oxide (iNO) has been shown to be an effective treatment for PPHN. [7][8][9][10] Several randomized clinical trials have shown that iNO significantly improves oxygenation and decreases the need of ECMO or incidence of death in near-term infants with hypoxic respiratory failure. [11][12][13] However, their response to iNO is not ideal and ranges between 50 and 60%.…”
Section: Introductionmentioning
confidence: 99%